Awareness and usage of emergency contraceptive pills among working women: a hospital based survey from north India - Harne, Prateek; Khan, Amir Maroof (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: In spite of the decline observed in total fertility rate (TFR) in India during the last few decades, the unintended pregnancy rates continue to remain the same. With increasing employment levels of women, there has been an increase in the contraceptive usage rates, but evidence among the working women regarding the emergency contraceptive pills is lacking. The Objectives of the study was to assess, among the working women regarding the emergency contraceptive pills (ECP). Methods: A cross sectional survey was conducted among the reproductive age group working women attending the obstetrics and gynecology outpatient department clinic of a private hospital in Delhi. Face to face interviews were conducted using a sem-structured questionnaire. Results: Out of the 206 participants studied, around one-third (35.0%) were not aware about ECPs. Amongst the aware, 81.3% and 44.8 % did not know about the correct indication and correct timing of ECP use respectively. Amongst those who were aware about ECPs, 91.8% had never used it. Conclusions: Even though the awareness about ECPs is not low, the correct knowledge about its indications and correct timing is poor. More emphasis on increasing the awareness about ECPs is required to increase its correct use thereby reducing TFR further.